Aspects of meaning construction - Radden, Günter (John Benjamins, 2007)
"England and America are two nations divided by a common language."(George Bernard Shaw)Adopting a construction-based view of language (Goldberg 1995), we demonstrate that it is possible to uncover differences between British and American English at the lexicosyntactic level, showing that the collexemes, i.e. the words significantly associated with a construction, are variety-dependent. To this end, we compare more than 5,000 verb pair types as they occur in the two varieties in the so-called into- causative construction (as in He tricked me into employing him) and submit them to